Stem Cell-Derived Exosomes Ameliorate Doxorubicin-Induced Muscle Toxicity through Counteracting Pyroptosis - Fatima Bianca A. Dessouki; Rakesh C. Kukreja; Dinender K. Singla (MDPI AG, 2020)
Doxorubicin (Dox)-induced muscle toxicity (DIMT) is a common occurrence in cancer patients; however, the cause of its development and progression is not established. We tested whether inflammation-triggered cell death, "pyroptosis" plays a role in DIMT. We also examined the potential role of exosomes derived from embryonic stem cells (ES-Exos) in attenuating DIMT. C57BL/6J mice (10 ± 2 wks age) underwent the following treatments: Control (saline), Dox, Dox+ES-Exos, and Dox+MEF-Exos (mouse-embryonic fibroblast-derived exosomes, negative control). Our results demonstrated that Dox significantly reduced muscle function in mice, which was associated with a significant increase in NLRP3 inflammasome and initiation marker TLR4 as compared with controls. Pyroptosis activator, ASC, was significantly increased compared to controls with an upregulation of specific markers (caspase-1, IL-1β, and IL-18). Treatment with ES-Exos but not MEF-Exos showed a significant reduction in inflammasome and pyroptosis along with improved muscle function. Additionally, we detected a significant increase in pro-inflammatory cytokines (TNF-α and IL-6) and inflammatory M1 macrophages in Dox-treated animals. Treatment with ES-Exos decreased M1 macrophages and upregulated anti-inflammatory M2 macrophages. Furthermore, ES-Exos showed a significant reduction in muscular atrophy and fibrosis. In conclusion, these results suggest that DIMT is mediated through inflammation and pyroptosis, which is attenuated following treatment with ES-Exos.